Монгол орны холимог металын металлогений асуудалд - Д., Доржготов; Б., Тамир (Geological Issues, 2022)
In Mongolia, around 40 deposits of polymetals and 250 occurrences about have been identifie, and they are very different from each other in terms of origin, geological formation, ore composition, and geological and mineralogical characteristics. This of types skarn polymetal, plutonogenic hydrothermal polymetal, volcanogenic hydrothermal massiv sulfide polymetal, volcanogenic hydrothermal massiv sulfide copper-zinc and volcanogenic hydrothermal massiv sulfide lead-silver five production types and one auxiliary type of zinc-lead stratiform are covered. Those kind of deposits and production type of polymetal production were formed during six periods of intense rejuvenated metallogenic from west to east during the period from Proterozoic to Mesozoic, and more than 80% of industrial reserves are estimated in Mesozoic deposits. The distribution and location of polymetals in Mongolia is defined by six metallogenic regions, 13 regions, and 24 districts, which differ in parameters such as tectonic structure type, geological formation, deposit type, etc.